Pacbio sequencing of copper-tolerant Xanthomonas citri reveals presence of a chimeric plasmid structure and provides insights into reassortment and shuffling of transcription activator-like effectors among X. citri strains - Gochez, Alberto Martin; Huguet-Tapia, Jose Carlos; Minsavage, Gerald V.; Shantharaj, Deepak; Jalan, Neha; Strauß, Annett; Lahaye, Thomas; Wang, Nian; Canteros, Blanca Isabel; Jones, Jeffrey B.; Potnis, Neha (BioMed Central, 2018)
Background: Xanthomonas citri, a causal agent of citrus canker, has been a well-studied model system due to recent availability of whole genome sequences of multiple strains from different geographical regions. Major limitations in our understanding of the evolution of pathogenicity factors in X. citri strains sequenced by short-read sequencing methods have been tracking plasmid reshuffling among strains due to inability to accurately assign reads to plasmids, and analyzing repeat regions among strains. X. citri harbors major pathogenicity determinants, including variable DNA-binding repeat region containing Transcription Activator-like Effectors (TALEs) on plasmids. The long-read sequencing method, PacBio, has allowed the ability to obtain complete and accurate sequences of TALEs in xanthomonads. We recently sequenced Xanthomonas citri str. Xc-03-1638-1-1, a copper tolerant A group strain isolated from grapefruit in 2003 from Argentina using PacBio RS II chemistry. We analyzed plasmid profiles, copy number and location of TALEs in complete genome sequences of X. citri strains. Results: We utilized the power of long reads obtained by PacBio sequencing to enable assembly of a complete genome sequence of strain Xc-03-1638-1-1, including sequences of two plasmids, 249 kb (plasmid harboring copper resistance genes) and 99 kb (pathogenicity plasmid containing TALEs). The pathogenicity plasmid in this strain is a hybrid plasmid containing four TALEs. Due to the intriguing nature of this pathogenicity plasmid with Tn3-like transposon association, repetitive elements and multiple putative sites for origins of replication, we might expect alternative structures of this plasmid in nature, illustrating the strong adaptive potential of X. citri strains. Analysis of the pathogenicity plasmid among completely sequenced X. citri strains, coupled with Southern hybridization of the pathogenicity plasmids, revealed clues to rearrangements of plasmids and resulting reshuffling of TALEs among strains. Conclusions: We demonstrate in this study the importance of long-read sequencing for obtaining intact sequences of TALEs and plasmids, as well as for identifying rearrangement events including plasmid reshuffling. Rearrangement events, such as the hybrid plasmid in this case, could be a frequent phenomenon in the evolution of X. citri strains, although so far it is undetected due to the inability to obtain complete plasmid sequences with short-read sequencing methods.